PENGARUH PENGELOLAAN KAWASAN HUTAN TERHADAP ASPEK EKONOMI DAN SOSIAL PADA KELOMPOK PERHUTANAN SOSIAL BATU AKIK KECAMATAN SEKONGKANG - LALU ADITYA PANDU ROSY KUMBARA; UMAR UMAR; MUAMMAR KHADAFIE (Universitas Mahasaraswati K. Mataram, 2024)
The social forestry program aims to empower communities in managing forest areas sustainably and improving their welfare. KTH Batu Akik, one of the social forestry groups in Talonang Baru Village, Sekongkang District, West Sumbawa, manages 200 hectares of forest through an agroforestry system that combines timber and food crops. This research aims to analyze the economic feasibility and social impact of forest management by KTH Batu Akik through the agroforestry system. A mixed-method approach was used, with respondents selected through purposive sampling. Qualitative data was collected through in-depth interviews, while quantitative data was obtained from questionnaires and analyzed using validity, reliability, normality, linearity tests, as well as correlation analysis and hypothesis testing. The results show that agroforestry increased members' income by up to 30%, with a correlation between technical variables and income of 0.559, and between environment and income of 0.642. Despite challenges in market access and infrastructure, forest management has proven economically viable and has had a positive social impact. Additional support, particularly in marketing and technical guidance, is needed for the sustainability of this program.